2022
DOI: 10.3390/ijerph19041912
|View full text |Cite
|
Sign up to set email alerts
|

General Practice Statistics in Australia: Pushing a Round Peg into a Square Hole

Abstract: In Australia, general practice forms a core part of the health system, with general practitioners (GPs) having a gatekeeper role for patients to receive care from other health services. GPs manage the care of patients across their lifespan and have roles in preventive health care, chronic condition management, multimorbidity and population health. Most people in Australia see a GP once in any given year. Draft reforms have been released by the Australian Government that may change the model of general practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Based on the 2019 estimate of 8147 general practice clinics in Australia, about 2.6% of all general practices have been purchased by private equity owners since 2017 (including practices sold by one private equity owner to another, but adjusted for the 43 practices acquired twice). 14 Given the scale of private equity investment in health care, more should be done to assess its local impact, particularly as American studies have identified negative outcomes in some contexts. Major differences between the payment and delivery characteristics of health systems mean, however, that extrapolating the findings of overseas studies to Australia is unlikely to valid.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the 2019 estimate of 8147 general practice clinics in Australia, about 2.6% of all general practices have been purchased by private equity owners since 2017 (including practices sold by one private equity owner to another, but adjusted for the 43 practices acquired twice). 14 Given the scale of private equity investment in health care, more should be done to assess its local impact, particularly as American studies have identified negative outcomes in some contexts. Major differences between the payment and delivery characteristics of health systems mean, however, that extrapolating the findings of overseas studies to Australia is unlikely to valid.…”
Section: Discussionmentioning
confidence: 99%
“…This unique partnership offered a publicly accessible dataset and provided information to participating pharmaceutical companies on their products' uses. The paper by Gordon et al [28] in this issue outlines the development and uses of this data collection.…”
Section: Primary Health Carementioning
confidence: 99%
“…Primary care teams include general practitioners (GPs), nurses. and allied health workers, 18 with GPs holding the position of the most frequently consulted health professionals in Australia, 19 where the average individual consults their GP approximately six times annually 20 . Despite this frequency, dementia topics often receive inadequate attention within primary care settings, leading to underdiagnosis.…”
Section: Introductionmentioning
confidence: 99%